What lies beneath data (base) considerations for service oriented architectures. - Chandras, Rajan
How important are data considerations to service oriented architectures (SOA) vending Web services? Consider the following definition of Web services from AMR Research : "Web services have been commonly defined as a standardized way of integrating applications using Extensible Markup Language (XML), Simple Object Access Protocol (SOAP), Web Services Definition Language (WSDL), and Universal Description, Discovery and Integration (UDDI) standards. XML is used to tag the data; SOAP is used to transfer the data; WSDL is used for describing the services available; and UDDI is used for listing what services are available.